1987
DOI: 10.1111/j.1469-8137.1987.tb00181.x
|View full text |Cite
|
Sign up to set email alerts
|

The Degradation of Chlorophyll — A Biological Enigma

Abstract: Summary Some 109tonnes of chlorophyll are destroyed each year on land and in the oceans. The fate of these chlorophylls is, however, largely unknown. This review describes the developmental stages at which chlorophyll breakdown occurs in aquatic and terrestrial biological systems, and the destruction arising from herbivory, disease, pollution and other physical hazards. At the cellular level, an attempt is made to separate the breakdown of chlorophyll during senescence from the many other events associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
236
3
17

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(259 citation statements)
references
References 201 publications
3
236
3
17
Order By: Relevance
“…For instance, silkworm excretes up to four different chlorophyll derivatives, of which two were identified as 13 2 -HO phaeophytin a and b (Nakatani et al 1981). Pigment concentrations from guts of nematodes feeding on microphytobenthic organisms (Majdi et al 2012) and caterpillars feeding on plants (Shao et al 2011) show the presence of chlorophyll and chlorophyll breakdown products (e.g., pheophorbide a and pheophytin a) (Hendry et al 1987). The two-spotted spider mite, a polyphagous species that feeds on more than 1,100 host plants, sucks the plant cell content of leaf mesophyll ( Van der Geest 1985).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, silkworm excretes up to four different chlorophyll derivatives, of which two were identified as 13 2 -HO phaeophytin a and b (Nakatani et al 1981). Pigment concentrations from guts of nematodes feeding on microphytobenthic organisms (Majdi et al 2012) and caterpillars feeding on plants (Shao et al 2011) show the presence of chlorophyll and chlorophyll breakdown products (e.g., pheophorbide a and pheophytin a) (Hendry et al 1987). The two-spotted spider mite, a polyphagous species that feeds on more than 1,100 host plants, sucks the plant cell content of leaf mesophyll ( Van der Geest 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering identification and structure determination of the first (final) Chl breakdown product, a NCC from barley, named Hv-NCC-1, in 1991 (Kräutler et al 1991) marked a milestone in the elucidation of Chl breakdown, which until then was described as 'biological enigma' (Hendry et al 1987;Brown et al 1991). To date more than 15 structures of NCCs have been identified from over 10 plant species.…”
Section: Nccs the Final Chlorophyll Breakdown Productsmentioning
confidence: 99%
“…It was reported that fruit ripening or senescence was also related to the accumulation of lipofuscin-like substance in pear [4], banana [4,15] and litchi [5]. Hendry, Houghton & Brown [16] proposed the presence of lipofuscin-like substance in living tissue and speculated that lipofuscin-like substance in senescent plant tissue may involve in the breakdown products of chlorophyll originating from methane bridge carbon attached to two halves of pyrroles of macrocyclic ring. Düggelin, Bortlik, Gut, Matile & Thomas [7] observed the different accumulation of lipofuscin-like substance in leaves of Festuca pratensis cv.…”
Section: Resultsmentioning
confidence: 99%